Anode active material, method for producing anode active material, anode composition, anode for lithium secondary battery including the same, and anode including the same

The surface area of ​​the silicon-based active material is adjusted by chemically generating crystal nuclei, which solves the problem of cutting the conductive path caused by volume expansion during charge and discharge of the silicon-based negative electrode material, and improves the life of the electrode and battery performance.

JP2025504084AActive Publication Date: 2025-02-06LG ENERGY SOLUTION LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024545845
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-01
Filing Date
2023-08-02
Publication Date
2025-02-06
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

In the prior art, the volume expansion of the silicon-based negative electrode active material during charging and discharging causes the conductive path to be cut off, affecting the performance of the battery and limiting its commercial application.

Method used

The crystal nucleus is generated by chemical methods, and the surface area and roughness of the silicon-based active material are adjusted so that its surface area is within the range of 0.30m²/g to 4.00m²/g, which enhances the binding force with the adhesive and reduces the occurrence of cracks during the charge and discharge cycle.

Benefits of technology

It improves the life retention rate of the electrode, ensures that the silicon-based active materials react uniformly during charging and discharging, reduces the occurrence of particle cracks, and improves the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504084000001_ABST
    Figure 2025504084000001_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode active material, a method for producing a negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0097513, filed with the Korean Intellectual Property Office on August 4, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode active material, a method for producing a negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is the field of power generation and storage using electrochemical reactions.

[0004] At present, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the range of its use is expanding more and more.

[0005] With the development of technology and increasing demand for mobile devices, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and widely used. In addition, research on methods for manufacturing high-density electrodes with higher energy density per unit volume as electrodes for such high-capacity lithium secondary batteries is being actively conducted.

[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode, and silicon-based particles having a large discharge capacity can be used as the negative electrode active material.

[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, while silicon-based compounds, which are high-capacity materials, have a larger capacity than conventionally used graphite, they have the problem that their volume expands rapidly during charging, cutting off the conductive path and degrading the battery characteristics.

[0008] In order to solve the problems when using silicon-based compounds as negative electrode active materials, various methods have been discussed, such as a method of adjusting the driving potential, a method of additionally coating a thin film on the active material layer, a method of controlling the particle size of the silicon-based compound, and a method of suppressing the volume expansion itself, or a variety of methods of preventing the conductive path from being broken. However, in the case of the above methods, there is a possibility that the performance of the battery may be deteriorated, so there is a limit to the application, and there is still a limit to the commercialization of the manufacture of negative electrode batteries with a high content of silicon-based compounds.

[0009] Therefore, even when a silicon-based active material is used as a negative electrode active material to improve capacity performance, research is needed into silicon-based active materials themselves that can prevent the conductive path from being interrupted due to the volume expansion of the silicon-based compound. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Patent Publication No. 2009-080971 Summary of the Invention [Problem to be solved by the invention]

[0011] A silicon-based active material is produced by a chemical processing method rather than a conventional grinding processing method. In particular, in the case of a silicon-based active material grown by the formation of crystal nuclei, it has been found by research that the surface area and roughness can be adjusted. By adjusting the surface area within a predetermined range, it has been confirmed that during the insertion / desorption reaction of lithium, the reaction occurs uniformly, reducing the stress on the silicon-based active material.

[0012] This application relates to a negative electrode active material, a method for manufacturing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode, which can solve the above problems.

Means for Solving the Problems

[0013] One embodiment of this specification is a silicon-based active material having a specific surface area of 0.30 m 2 / g or more and 4.00 m 2 / g or less. The silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2). Based on 100 parts by weight of the silicon-based active material, it provides a negative electrode active material containing 70 parts by weight or more of the SiOx (x = 0).

[0014] In another embodiment, a method for manufacturing a negative electrode active material includes: chemically reacting silane gas to deposit a silicon-based active material on a substrate; growing the silicon-based active material by the formation of crystal nuclei; and obtaining the silicon-based active material deposited on the substrate. The specific surface area of the silicon-based active material is 0.30 m 2 / g or more and 4.00 m 2 / g or less. It provides a method for manufacturing a negative electrode active material according to this application.

[0015] In another embodiment, it provides a negative electrode composition including a negative electrode active material according to this application, a negative electrode conductive material, and a negative electrode binder.

[0016] In another embodiment, a negative electrode for a lithium secondary battery is provided, which includes a negative electrode current collector layer; and a negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer contains the negative electrode composition according to the present application or a cured product thereof.

[0017] Finally, a lithium secondary battery is provided, which includes a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

Advantages of the Invention

[0018] In the case of the negative electrode active material according to one embodiment of the present invention, different from the conventional pulverization processing method, a chemical method is used, and a silicon-based active material is grown by the generation of crystal nuclei. Thus, it is characterized by having a silicon-based substance with a specific surface area of more than a predetermined range.

[0019] The negative electrode active material of the present invention includes, as a silicon-based active material, one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2). Based on 100 parts by weight of the silicon-based active material, it contains 70 parts by weight or more of the SiOx (x = 0), that is, while having a pure silicon (Pure Si) active material, the main feature is that the problem of volume expansion due to charge and discharge, which is a problem caused by this, is solved by adjusting the specific surface area of the silicon-based active material to a predetermined range.

[0020] That is, by using a silicon-based active material whose specific surface area satisfies the range according to the present invention, the rough surface enables the particles having the same particle size to have a large surface area, and the binding force with the binder becomes high, thereby relaxing the cracks (Crack) of the electrode due to repeated charge and discharge cycles. Also, it can react uniformly during the insertion and desorption reactions of lithium during charge and discharge, reducing the stress received by the silicon-based active material and relaxing the cracking of the particles, thereby improving the life maintenance rate of the electrode.

Brief Description of the Drawings

[0021] [Figure 1] FIG. 2 is a diagram showing a manufacturing process of a silicon-based active material according to Example 1 of the present application. [Diagram 2] FIG. 2 is a diagram showing a manufacturing process of a silicon-based active material according to Comparative Example 1 of the present application. [Diagram 3] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Figure 4] FIG. 1 is a diagram showing a stacked structure of a lithium secondary battery according to an embodiment of the present application. [Diagram 5] 1 illustrates the concept of sphericity of silicon-based active materials. [Figure 6] The concept of convexity of silicon-based active materials is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Before describing the present invention, some terms will first be defined. In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.

[0023] In this specification, "p to q" means "greater than or equal to p and less than or equal to q." In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area can mean the specific surface area measured by the above-mentioned measurement method.

[0024] In this specification, "Dn" means particle size distribution, and refers to the particle size at n% of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at 50% of the cumulative particle number distribution by particle size, D90 is the particle size at 90% of the cumulative particle number distribution by particle size, and D10 is the particle size at 10% of the cumulative particle number distribution by particle size. Meanwhile, the average particle size may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and when the particles pass through a laser beam, the difference in the diffraction pattern due to the particle size is measured to calculate the particle size distribution.

[0025] In one embodiment of the present application, the grain size or grain size may refer to the average grain size or representative grain size of each grain constituting the metal powder.

[0026] In the present specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer participates in a polymerization reaction and is contained as a repeating unit in the polymer. In the present specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.

[0027] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer".

[0028] In this specification, the weight average molecular weight (Mw) and number average molecular weight (Mn) are polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight average molecular weight unless otherwise specified.

[0029] Hereinafter, for those with ordinary knowledge in the technical field to which the present invention pertains to be able to easily implement the present invention, a detailed description will be given with reference to the drawings. However, the present invention can be embodied in various different forms and is not limited to the following description.

[0030] One embodiment of this specification has a silicon-based active material with a specific surface area of 0.30 m 2 / g or more and 4.00 m 2 / g or less. The silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2). Based on 100 parts by weight of the silicon-based active material, it provides a negative electrode active material containing 70 parts by weight or more of the SiOx (x = 0).

[0031] The negative electrode active material of the present invention includes, as the silicon-based active material, one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2). Based on 100 parts by weight of the silicon-based active material, it contains 70 parts by weight or more of the SiOx (x = 0). That is, while having a pure silicon (Pure Si) active material, the main feature is that the problem of volume expansion due to charge and discharge, which is a problem caused by it, is solved by adjusting the specific surface area of the silicon-based active material to a predetermined range.

[0032] That is, by using a silicon-based active material whose specific surface area satisfies the range according to the present invention, the rough surface makes the particles with the same particle size have a wider surface area, and the binding force with the binder becomes higher, thereby relaxing the cracks of the electrode due to repeated charge and discharge cycles. Also, it can react uniformly during the insertion and desorption reactions of lithium during charge and discharge, reducing the stress received by the silicon-based active material and relaxing the cracking of the particles, thereby improving the electrode life maintenance rate.

[0033] In one embodiment of the present application, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more.

[0034] In one embodiment of the present application, the silicon-based active material includes SiOx (x = 0), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more.

[0035] In another embodiment, based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be included in an amount of 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0036] In one embodiment of the present application, pure silicon (Si) particles may be used as the silicon-based active material. Using pure silicon (Si) particles as the silicon-based active material may mean, as described above, that pure Si particles (SiOx (x = 0)) not bonded to other particles or elements are included within the above range based on 100 parts by weight of the entire silicon-based active material.

[0037] In one embodiment of the present application, the silicon-based active material may be composed of silicon-based particles having 100 parts by weight of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material.

[0038] In one embodiment of the present application, the silicon-based active material may contain metal impurities. In this case, the impurities are metals that may generally be contained in the silicon-based active material. Specifically, based on 100 parts by weight of the silicon-based active material, the amount may be 0.1 part by weight or less.

[0039] Silicon-based active materials have a significantly higher capacity than conventional graphite-based active materials, and efforts to use them are increasing. However, they have a high volume expansion rate during charging and discharging, so they are only used in small amounts in graphite-based active materials.

[0040] Therefore, in the case of the present invention, in order to improve capacity performance, only a silicon-based active material is used as a negative electrode active material, but in order to solve the above-mentioned problems, the conventional problems are solved by adjusting the surface area (surface roughness) of the silicon-based active material itself rather than adjusting the composition of the conductive material and binder.

[0041] In one embodiment of the present application, the negative electrode active material has a specific surface area of ​​0.30 m 2 / g or more 4.00m 2 / g or less of a silicon-based active material.

[0042] In another embodiment, the silicon-based active material has a specific surface area of ​​0.30 m 2 / g or more, preferably 0.31m 2 / g or more, more preferably 0.32m 2 The silicon-based active material may have a specific surface area of ​​4.00 m 2 / g or less, preferably 2.50m 2 / g or less, more preferably 2.20m 2 The specific surface area may be measured according to DIN 66131 (with nitrogen) in accordance with the following range:

[0043] The silicon-based active material has the specific surface area, and the surface area of ​​the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process and the growth conditions of the silicon-based active material, which will be described later. That is, when the negative electrode active material is manufactured by the manufacturing method according to the present application, the rough surface has a large surface area relative to particles having the same particle size, and at this time, the above range is satisfied, and the binding force with the binder is increased, thereby reducing cracks in the electrode caused by repeated charge and discharge cycles.

[0044] In addition, lithium ions are uniformly inserted during insertion, so that the stress applied to the silicon particles during insertion of lithium ions can be reduced, and thus particle cracking can be alleviated. As a result, the negative electrode has the characteristic of being able to improve its life stability. If the specific surface area is less than the above range, even if the particle size is the same, the surface is formed smoothly, and the binding force with the binder is reduced, causing electrode cracks. In this case, lithium ions are inserted non-uniformly within the particles, and the stress due to ion insertion is large, causing particle cracking. In one embodiment of the present application, the SiOx (x=0) has a crystal grain size of 200 nm or less. When a silicon-based active material having a crystal grain size satisfying the above range is used, lithium can react uniformly during insertion and desorption reactions during charging and discharging, and the stress applied to the silicon-based active material can be reduced, thereby alleviating particle cracking, thereby improving the life maintenance rate of the electrode.

[0045] In this application, the term "crystal grain" refers to a crystal particle in a metal or material that is composed of an irregularly shaped aggregate of microscopic particles, and the term "crystal grain size" may refer to the diameter of the observed crystal grain. That is, in this application, the term "crystal grain size" refers to the size of a domain that shares the same crystal orientation within a particle, and has a different concept from the grain size or grain size that expresses the size of a substance.

[0046] In another embodiment, the crystal grain size of the silicon-based active material may be 200 nm or less, preferably 130 nm or less, more preferably 110 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, more specifically 91 nm or less. The crystal grain size of the silicon-based active material may be 1 nm or more, preferably 3 nm or more.

[0047] The SiOx (x=0) has the above grain size, and the grain size can be adjusted by changing the process conditions in the manufacturing process described below. In this case, by satisfying the above range, the grain boundaries are widely distributed, and lithium ions are uniformly inserted during insertion, so that the stress applied during insertion of lithium ions into silicon particles can be reduced, and thus particle cracking can be alleviated. As a result, the negative electrode has the characteristic of improving the life stability. If the grain size exceeds the above range, the grain boundaries within the particles are narrowly distributed, and in this case, lithium ions within the particles are non-uniformly inserted, and the stress due to ion insertion is large, causing particle breakage.

[0048] In one embodiment of the present application, there is provided a negative electrode active material, wherein the silicon-based active material includes a crystalline structure having a crystal grain distribution of 1 nm or more and 200 nm or less, and an area ratio of the crystalline structure is 5% or less based on the total area of ​​the silicon-based active material.

[0049] In still another embodiment, the area ratio of the crystalline structure may be 5% or less, 3% or less, or 0.1% or more, based on the total area of ​​the silicon-based active material.

[0050] That is, the silicon-based active material according to the present application has a crystal grain size of 200 nm or less, and the size of each crystal structure is small, so that the above-mentioned area ratio can be satisfied, and thus the distribution of grain boundaries can be broadened, thereby achieving the above-mentioned effects.

[0051] In one embodiment of the present application, the silicon-based active material provides a negative electrode active material that satisfies the range of the following formula 1. [Formula 1] X1 / Y1≦0.960 In formula 1, X1 is the orthogonal projected area of ​​the silicon-based active material, Y1 means the area of ​​a circle having the same circumference as the orthogonal projection of the silicon-based active material

[0052] The formula 1 can be measured using a particle size analyzer. Specifically, the silicon-based active material according to the present application is dispersed on a glass plate by air injection, and the dispersed silicon-based active material particles are orthogonally projected in a photograph, and the particle sizes of 10,000 silicon-based active material particles in the photograph can be measured. In this case, the formula 1 is a value expressing the average for 10,000 particles. The formula 1 according to the present application can be measured from the image, and the formula 1 can be expressed as the circularity of the silicon-based active material. The concept of sphericity is shown in FIG. 5. The sphericity can be calculated by the formula [4π*orthogonal projection area of ​​silicon-based active material / (orthogonal projection perimeter of silicon-based active material) 2 ] may also be displayed.

[0053] Alternatively, X1 may represent the actual area of ​​the silicon-based active material, and Y1 may represent the area of ​​a spherical particle around the silicon-based active material.

[0054] In one embodiment of the present application, the sphericity of the silicon-based active material may be, for example, 0.960 or less, for example, 0.957 or less. The sphericity of the silicon-based active material may be, for example, 0.8 or more, for example, 0.9 or more, specifically, 0.93 or more, more specifically, 0.94 or more, for example, 0.941 or more.

[0055] In one embodiment of the present application, the silicon-based active material provides a negative electrode active material that satisfies the range of the following formula 2. [Formula 2] X2 / Y2≦0.996 In the formula 2, Y2 is the orthogonal projection perimeter of the silicon-based active material, X2 is the perimeter of a polygon that circumscribes the orthogonal projection of the silicon-based active material.

[0056] The formula 2 may be measured using a particle shape analyzer. Specifically, the silicon-based active material according to the present application may be dispersed on a glass plate by air injection, and an orthogonal projection image of the dispersed silicon-based active material may be photographed to measure the particle shapes of 10,000 silicon-based active material particles in the photograph. In this case, the formula 2 is a value expressing an average for 10,000 particles. The formula 2 according to the present application may be measured from the image, and the formula 2 may be expressed as the convexity of the silicon-based active material. The concept of convexity is shown in FIG. 6.

[0057] Alternatively, Y2 may be the actual perimeter of the silicon-based active material, and X2 may be the perimeter of the circumscribing figure of the silicon-based active material.

[0058] In one embodiment of the present application, X2 / Y2 may satisfy the range of ≦0.996, preferably ≦X2 / Y2 ≦0.995, or may satisfy the range of 0.8≦X2 / Y2, preferably 0.9≦X2 / Y2, more preferably 0.95≦X2 / Y2, specifically 0.98≦X2 / Y2.

[0059] The smaller the value of Formula 1 or Formula 2, the greater the roughness of the silicon-based active material. By using a silicon-based active material having such a range, the bonding strength with the binder increases, and thus cracks in the electrode caused by repeated charge-discharge cycles can be alleviated.

[0060] In one embodiment of the present application, the negative electrode active material does not have a pore structure, satisfies Formula 1 and Formula 2, and has an outer surface irregularity. That is, the negative electrode active material may have an outer surface irregularity without having an internal pore structure.

[0061] In one embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.

[0062] The silicon-based active material containing silicon-based particles having a particle size distribution of 0.01 μm to 30 μm means that the silicon-based active material contains a large number of individual silicon-based particles having particle sizes within the above range, and the number of silicon-based particles contained is not limited.

[0063] The particle size of the silicon-based particles may be expressed as their diameter when they are spherical, but when they are other shapes than spherical, the particle size may be measured in comparison with the spherical case, and the particle size of individual silicon-based particles may be measured by methods commonly used in the art.

[0064] Meanwhile, the average particle size (D50 particle size) of the silicon-based active material of the present invention may be 3 μm to 10 μm, specifically, 5.5 μm to 8 μm, and more specifically, 6 μm to 7 μm. When the average particle size is within the above range, the specific surface area of ​​the particles is within an appropriate range, and the viscosity of the negative electrode slurry is formed within an appropriate range. As a result, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the size of the silicon-based active material is equal to or greater than the lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, and the capacity retention rate is increased. Meanwhile, when the average particle size satisfies the above range, silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the phenomenon of non-uniform current density during charging and discharging.

[0065] In one embodiment of the present application, the silicon-based active material may be present, for example, in crystalline or amorphous form, and is preferably not porous.The silicon particles are preferably spherical or multi-lobed particles.Alternatively, the silicon particles may have a fibrous structure or may be present in the form of a silicon-containing thin film or coating, but less preferably.

[0066] In one embodiment of the present application, there is provided a negative electrode composition comprising: the negative electrode active material; a negative electrode conductive material; and a negative electrode binder.

[0067] In one embodiment of the present application, there is provided a negative electrode composition, in which the negative electrode active material is 40 parts by weight or more based on 100 parts by weight of the negative electrode composition.

[0068] In yet another embodiment, the negative electrode active material may contain, based on 100 parts by weight of the negative electrode composition, 40 parts by weight or more, preferably 60 parts by weight or more, more preferably 65 parts by weight or more, and even more preferably 70 parts by weight or more, and may contain 95 parts by weight or less, preferably 90 parts by weight or less, and more preferably 85 parts by weight or less.

[0069] The negative electrode composition according to the present application uses a negative electrode active material that satisfies a specific surface area size that can control the volume expansion rate during charging and discharging even when a silicon-based active material with remarkably high capacity is used within the above range, and has the characteristics of excellent output characteristics during charging and discharging without deteriorating the performance of the negative electrode even when the above range is included.

[0070] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but recently, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based active materials to increase capacity have been increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active materials themselves are adjusted as described above, there are some cases where the volume of the silicon-based active materials rapidly expands during charging / discharging, causing a problem of breaking the conductive path formed in the negative electrode active material layer.

[0071] Therefore, in one embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of dot-like conductive materials, sheet-like conductive materials, and linear conductive materials.

[0072] In one embodiment of the present application, the dot-like conductive material refers to a dot-like or spherical conductive material that can be used to improve the conductivity of the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-like conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black in terms of realizing high conductivity and excellent dispersibility.

[0073] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of ​​40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.

[0074] In one embodiment of the present application, the dot-like conductive material may have a volatile matter content of 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.

[0075] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, the functional groups are present on the surface of the dot-shaped conductive material, and when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, by using a specific silicon-based active material in the present invention, the functional group content of the dot-shaped conductive material can be reduced, thereby having an excellent effect in improving dispersibility.

[0076] In one embodiment of the present application, the active material is characterized in that it contains a dot-shaped conductive material having a functional group content in the above range together with a silicon-based active material, and the functional group content can be adjusted by the degree of heat treatment of the dot-shaped conductive material.

[0077] In one embodiment of the present application, the particle size of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0078] In one embodiment of the present application, the conductive material may include a sheet-shaped conductive material. The planar conductive material can increase surface contact between silicon particles in the negative electrode to improve conductivity, and at the same time, can suppress disconnection of the conductive path due to volume expansion. The planar conductive material may be referred to as a plate-type conductive material or a bulk-type conductive material.

[0079] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may preferably be platelet graphite.

[0080] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically, 3 μm to 6 μm, and more specifically, 3.5 μm to 5 μm. If the above range is satisfied, the particle size is sufficient, so that the viscosity of the negative electrode slurry is not excessively increased, and dispersion is easy. Therefore, when dispersing using the same equipment and time, the dispersion effect is excellent.

[0081] In one embodiment of the present application, there is provided a negative electrode composition in which the sheet conductive material has a D10 of 0.5 μm or more and 2.0 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 6.5 μm or more and 15.0 μm or less.

[0082] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.

[0083] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material with a high specific surface area or a sheet conductive material with a low specific surface area without any restrictions. In particular, the sheet conductive material in the present application may be affected to some extent by the dispersion effect on the electrode performance, and it is particularly preferable to use a sheet conductive material with a low specific surface area in which dispersion problems do not occur.

[0084] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of ​​0.25 m 2 / g or more.

[0085] In another embodiment, the sheet conductive material has a BET specific surface area of ​​1 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g.

[0086] The sheet conductive material according to the present application may be a high specific surface area sheet conductive material; or a low specific surface area sheet conductive material.

[0087] In another embodiment, the sheet conductive material is a sheet conductive material having a high specific surface area and a BET specific surface area of ​​50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.

[0088] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of ​​1 m 2 / g or more 40m2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.

[0089] Alternatively, the conductive material may be a linear conductive material such as a carbon nanotube. The carbon nanotube may be a bundle-type carbon nanotube. The bundle-type carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in which a plurality of carbon nanotube units are arranged in parallel with the longitudinal axis of the carbon nanotube units being substantially aligned in the same direction or twisted into a bundle or rope. The carbon nanotube unit has a graphite sheet having a nano-sized cylindrical shape and an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure at which it is wound. The bundle-type carbon nanotube may be uniformly dispersed during the manufacture of the negative electrode compared to an entangled type carbon nanotube, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0090] In one embodiment of the present application, there is provided a negative electrode composition, in which the negative electrode conductive material is 20 parts by weight or less based on 100 parts by weight of the negative electrode composition.

[0091] In another embodiment, the negative electrode conductive material may contain, based on 100 parts by weight of the negative electrode composition, 0.1 parts by weight or more and 20 parts by weight or less, preferably 1 part by weight or more and 20 parts by weight or less, more preferably 5 parts by weight or more and 15 parts by weight or less, and most preferably 6 parts by weight or more and 13 parts by weight or less.

[0092] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application plays a role of controlling the contact between the silicon-based active material, which has a very large volume expansion of the electrode due to charging and discharging, and the positive electrode conductive material plays a role of providing some conductivity while acting as a buffer when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.

[0093] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.

[0094] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and role different from that of the carbon-based active material usually used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and means a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.

[0095] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape and may be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play a role in storing and releasing lithium, but rather a material to ensure a planar conductive path inside the negative electrode active material layer.

[0096] That is, in the present application, the use of plate-like graphite as a conductive material means that it is processed into a planar or plate-like shape and used as a material to ensure a conductive path rather than to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.

[0097] On the other hand, in the present application, the carbon-based active material being used as an active material means that it is processed into a dot-like or spherical shape and used as a material that plays a role in storing or releasing lithium.

[0098] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, is dot-shaped and has a BET specific surface area of ​​0.1 m 2 / g or more 4.5m 2 / g or less. The plate-shaped graphite, which is a planar conductive material, is planar and has a BET specific surface area of ​​5 m 2 / g or more.

[0099] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.

[0100] The negative electrode binder according to one embodiment of the present application plays a role of controlling the active material and conductive material in order to prevent twisting and deformation of the negative electrode structure during volume expansion and relaxation of the silicon-based active material. In the case where the above role is fulfilled, any conventional binder may be applied, specifically, a water-based binder may be used, and more specifically, a PAM-based binder may be used.

[0101] In one embodiment of the present application, the amount of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition, or may be 5 parts by weight or more, or 10 parts by weight or more.

[0102] According to one embodiment of the present application, there is provided a method for producing an anode active material, the method comprising the steps of: depositing a silicon-based active material on a substrate by chemically reacting a silane gas; growing the silicon-based active material by generating crystal nuclei; and obtaining the silicon-based active material deposited on the substrate, the silicon-based active material having a specific surface area of ​​0.30 m2. 2 / g or more 4.00m 2 / g or less.

[0103] According to an embodiment, the silane gas may include one or more gases selected from monosilane, dichlorosilane, and trichlorosilane, and may be, specifically, trichlorosilane gas.

[0104] In one embodiment of the present application, the step of growing the silicon-based active material by generating crystal nuclei may be performed under a temperature condition of 800° C. or more, preferably 800° C. to 1300° C., which is a lower temperature than the conventional gas atomizing method in which the silicon is heated to 1600° C. or more to melt the silicon. The step of growing the silicon-based active material by generating crystal nuclei may be performed under a pressure of 100 Pa to 150 Pa. The step of growing the silicon-based active material by generating crystal nuclei may be performed under a pressure of 100 Pa to 150 Pa, which is a lower temperature than the conventional gas atomizing method in which the silicon is heated to 1600° C. or more to melt the silicon.

[0105] Conventionally, MG-silicon, which is a silicon lump, is crushed by physical force to produce it. When produced in this way, the crystal grain size is generally over 100 nm, the surface is smooth, and the specific surface area is 0.30 m 2 / g. Simply put, when a silicon-based active material is manufactured using a conventional method, it is difficult to control the surface area, and therefore it is difficult to ensure the life stability of the negative electrode.

[0106] However, the method for producing the negative electrode active material according to the present application includes a step of silanizing the silicon chunks through a chemical reaction, and then growing the silicon-based active material through the generation of crystal nuclei, thereby forming silicon particles, thereby making it possible to obtain a silicon-based active material that satisfies the surface area requirements of the present application.

[0107] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer comprising the negative electrode composition according to the present application or a cured product thereof, formed on one or both sides of the negative electrode current collector layer.

[0108] 3 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 on one side of a negative electrode current collector layer 10 can be seen. Although FIG. 3 shows that the negative electrode active material layer is formed on one side, it may be formed on both sides of the negative electrode current collector layer.

[0109] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry containing the negative electrode composition to one or both surfaces of a negative electrode current collector layer, and drying the applied slurry.

[0110] In this case, the negative electrode slurry may include the negative electrode composition described above; and a slurry solvent.

[0111] In one embodiment of the present application, the solid content of the negative electrode slurry may be 5% or more and 40% or less.

[0112] In another embodiment, the solid content of the negative electrode slurry may be in the range of 5% to 40%, preferably 7% to 35%, and more preferably 10% to 30%.

[0113] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, or may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0114] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, and the caking phenomenon of particles of the negative electrode composition is minimized, thereby enabling the negative electrode active material layer to be efficiently formed.

[0115] In one embodiment of the present application, the slurry solvent may be any solvent capable of dissolving the negative electrode composition, and specifically, water or NMP may be used.

[0116] In one embodiment of the present application, the negative electrode current collector layer usually has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, plastic carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy may be used. In addition, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0117] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 5 μm or more and 500 μm or less.

[0118] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.

[0119] In one embodiment of the present application, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less.

[0120] In another embodiment, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0121] The porosity varies depending on the composition and content of the silicon-based active material, conductive material, and binder contained in the negative electrode active material layer, and in particular, the silicon-based active material and conductive material according to the present application are contained in specific compositions and content portions to satisfy the above range, thereby providing an electrode with appropriate ranges of electrical conductivity and resistance.

[0122] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

[0123] 4 is a diagram showing a laminated structure of a lithium secondary battery according to an embodiment of the present application. Specifically, a lithium secondary battery anode 100 including an anode active material layer 20 on one side of an anode current collector layer 10 can be seen, and a lithium secondary battery cathode 200 including a cathode active material layer 40 on one side of a cathode current collector layer 50 can be seen, and the lithium secondary battery anode 100 and the lithium secondary battery cathode 200 are laminated with a separator 30 sandwiched therebetween.

[0124] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0125] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0126] In the positive electrode, the positive electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery, and may be, for example, stainless steel, aluminum, nickel, titanium, plastic carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0127] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 Ni-site type lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M can be at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be metallic lithium (Li-metal).

[0128] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.

[0129] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0130] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.

[0131] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries may be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, a coated separator containing a ceramic component or a polymeric material to ensure heat resistance or mechanical strength may be used, and may be selectively used in a single layer or multilayer structure.

[0132] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these. Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0133] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0134] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are highly viscous organic solvents having a high dielectric constant and capable of dissociating lithium salts, and therefore can be preferably used. When such a cyclic carbonate is mixed with a chain carbonate having a low viscosity and a low dielectric constant, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore such a cyclic carbonate can be more preferably used.

[0135] The metal salt may be a lithium salt, and the lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte solution. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 -, CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0136] In addition to the constituents of the electrolyte, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in the capacity of the battery, and improving the discharge capacity of the battery.

[0137] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore may be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system. EXAMPLES

[0138] Below, preferred embodiments are presented to aid in understanding the present invention. However, these embodiments are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the claims.

[0139] <Production Example> <Production of negative electrode active materials in Examples 1 to 6> FIG. 1 is a diagram showing the manufacturing process of silicon-based active material according to Example 1 of the present application. Specifically, silicon chunks (MG-Si) were silane-gasified at high temperature, and then chemically reacted and deposited on a substrate, after which the silicon-based active material was grown by the generation of crystal nuclei. The results are shown in Table 1.

[0140] In this case, by controlling the process conditions (selecting the conditions for controlling the surface area in Table 1 below within the crystal nucleation temperature and pressure range, and adjusting the temperature and pressure conditions to control the surface area), the surface area of ​​the silicon-based active materials of Examples 1 to 6 can be controlled, and the results are shown in Table 1.

[0141] <Production of Negative Electrode Active Material of Comparative Example 1> 2 is a diagram showing a manufacturing process of a silicon-based active material according to Comparative Example 1 of the present application. Specifically, silicon blocks, MG-Si, were crushed and melted by physical force, and then gas atomized. As a result, a negative electrode active material with a relatively smooth surface formed due to the liquid / gas surface tension was manufactured, and the specific surface area, circularity, convexity, and D50 particle size of the silicon-based active material in this case are as shown in Table 1.

[0142] [Table 1]

[0143] In the case of Comparative Example 2, silicon chunks (MG-Si) were crushed by physical force, melted, and then gas atomized, followed by strong base etching to form a silicon-based active material having pores, the information of which is as shown in Table 1.

[0144] In addition, in the case of Comparative Example 3, the deposition type silicon-based active material was treated with a strong base to mainly form internal pores rather than surface irregularities. As a result, the specific surface area was higher than in the other Comparative Examples and Examples, and Equation 1 (circularity) showed an increased value and Equation 2 (convexity) showed a decreased value compared to Examples 1 to 6 of the present application.

[0145] That is, in Comparative Example 3, as in Comparative Example 2, pores are formed on the smooth surface, so the roughness increases significantly, but the nearly elliptical particles are scraped off and made circular.

[0146] As shown in Table 1, the silicon in Examples 1 to 6 has a specific surface area of ​​0.30 m 2 / g or more.

[0147] For reference, in the case of Comparative Example 3, in which pores are formed inside the silicon-based active material, which does not have a protruding uneven shape on the surface of the silicon-based active material, a silicon-based active material with a smooth surface is formed as in Comparative Example 1, and pores are formed by a strong base etching method, so that the specific surface area is larger than those of Examples 1 to 6, and Convexity is also larger. This is because, when pores are formed, as the roughness of the existing smooth surface increases, Convexity decreases, but it is considered that some particles that are close to an elliptical shape are scraped off and made circular during the etching process.

[0148] <Production of negative electrodes> The negative electrode active material including the silicon-based active material in Table 1, the negative electrode conductive material, and polyacrylamide as a binder were added to distilled water as a solvent for forming a negative electrode slurry in a weight ratio of 80:10:10 to prepare a negative electrode slurry (solid concentration: 25 wt %).

[0149] Specifically, the negative electrode conductive material is carbon black (specific surface area: 45 m 2 / g, diameter: 30 nm to 50 nm).

[0150] As a specific mixing method, the negative electrode conductive material, binder, and water were dispersed at 2500 rpm for 30 minutes using a homomixer, and then the silicon-based active material was added and dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.

[0151] The negative electrode current collector layer was prepared by applying the negative electrode slurry at 85 mg / 25 cm to both sides of a copper current collector (thickness: 8 μm). 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (negative electrode thickness: 41 μm, negative electrode porosity: 40.0%).

[0152] <Secondary battery manufacturing> As the positive electrode active material, LiNi 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).

[0153] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) on both sides of which the positive electrode slurry was applied at 537 mg / 25 cm. 2The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).

[0154] A polyethylene separator was interposed between the positive electrode and the negative electrode of each of the examples and comparative examples, and an electrolyte was injected to prepare a lithium secondary battery.

[0155] The electrolyte was prepared by adding vinylene carbonate to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed in a volume ratio of 10:90, at a concentration of 3% by weight based on the total weight of the electrolyte, and adding LiPF6 as a lithium salt at a concentration of 1M.

[0156] <Experimental Example> Experimental example 1: Monocell life performance results The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention. The secondary batteries were subjected to an in-situ cycle test at 4.2-3.0V, 1C / 0.5C. During the test, the secondary batteries were charged / discharged at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and the capacity retention was measured. Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at first cycle)} x 100

[0157] [Table 2]

[0158] As can be seen from Table 2, when checking the capacity retention rate due to cycles in Examples 1 to 6 and Comparative Examples 1 to 3, it was confirmed that the capacity retention rate in Comparative Example 1 was lower than that of the Examples. This corresponds to the result that when the specific surface area size of the silicon-based active material satisfies the range according to the present invention, the lithium insertion and desorption reaction during charging and discharging can be uniformly reacted, the stress received by the silicon-based active material can be reduced, and cracking of the particles can be alleviated, thereby improving the capacity retention rate of the electrode.

[0159] Experimental example 2: Monocell resistance increase rate In the test of Experimental Example 1, the capacity retention rate was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at a pulse of 2.5C at SOC50, and the resistance increase rate was compared and analyzed. For the measurement and evaluation of the resistance increase rate, data at 200 cycles was calculated, and the results are shown in Table 3 below.

[0160] [Table 3]

[0161] From Tables 2 and 3, it was possible to confirm that the batteries using the silicon produced in Examples 1 to 6 as the negative electrode active material had excellent life characteristics and resistance change.

[0162] Furthermore, in the case of Comparative Example 2, the specific surface area is smaller than that of the present invention, and corresponds to a structure having internal pores rather than an externally uneven form. In this case, it is judged to be more effective than Comparative Example 1, whose specific surface area is far outside the range of the present invention, but it was confirmed that the internal pore form caused a decrease in life performance and a large change in resistance compared to this example.

[0163] For reference, in the case of Comparative Example 3, pores were formed inside the silicon-based active material, which does not have a protruding uneven shape on the surface of the silicon-based active material, and corresponds to the case of forming a silicon-based active material with a smooth surface as in Comparative Example 2, and forming pores by a strong base etching method. As a result, it can be confirmed that the specific surface area was formed larger than in Examples 1 to 6, and that the formula 1 was formed larger. In this case, it was confirmed that the life performance was reduced and the resistance change was large compared to this example by showing the internal pore form similar to Comparative Example 2. [Explanation of symbols]

[0164] 10 Negative electrode current collector layer 20...Negative electrode active material layer 30 Separator 40...Cathode active material layer 50 Positive electrode current collector layer 100 ···Negative electrode for lithium secondary battery 200 ···Positive electrode for lithium secondary batteries

Claims

1. Specific surface area is 0.30m 2 / g or more 4.00m 2 / g or less of a silicon-based active material, The silicon-based active material includes one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and the silicon-based active material includes 70 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material.

2. The negative electrode active material according to claim 1 , wherein the SiO x (x=0) has a crystal grain size of 200 nm or less.

3. The negative electrode active material according to claim 1, wherein the silicon-based active material satisfies the range of the following formula 1: [Formula 1] X1 / Y1≦0.960 In the above formula 1, X1 is the orthogonal projection area of ​​the silicon-based active material; Y1 means the area of ​​a circle having the same circumference as the orthogonal projection of the silicon-based active material.

4. The negative electrode active material according to claim 1 , wherein the silicon-based active material satisfies the range of the following formula 2: [Formula 2] X2 / Y2≦0.996 In the formula 2, Y2 is the orthogonal projection perimeter of the silicon-based active material; X2 is the perimeter of a polygon that circumscribes the orthogonal projection of the silicon-based active material.

5. The negative electrode active material according to claim 1 , wherein the silicon-based active material has a D50 particle size of 3 μm or more and 10 μm or less.

6. depositing a silicon-based active material on the substrate by chemically reacting the silane gas; Growing the silicon-based active material by generating crystal nuclei; and obtaining the silicon-based active material deposited on the substrate; A method for producing a negative electrode active material, comprising: The specific surface area of ​​the silicon-based active material is 0.30 m 2 / g or more 4.00m 2 The method for producing a negative electrode active material according to any one of claims 1 to 5, wherein the surface area of ​​the negative electrode active material is 0.1 μm or less.

7. The method for producing a negative electrode active material according to claim 6 , wherein the silane gas contains one or more gases selected from monosilane, dichlorosilane, and trichlorosilane.

8. 7. The method of claim 6, wherein the step of growing the silicon-based active material by generating crystal nuclei is performed at a temperature of 800° C. to 1300° C. and a pressure of 100 Pa to 150 Pa.

9. A negative electrode composition comprising the negative electrode active material according to any one of claims 1 to 5, a negative electrode conductive material, and a negative electrode binder.

10. The negative electrode composition according to claim 9 , wherein the negative electrode active material is present in an amount of 40 parts by weight or more based on 100 parts by weight of the negative electrode composition.

11. The negative electrode composition according to claim 9 , wherein the negative electrode conductive material is present in an amount of 20 parts by weight or less based on 100 parts by weight of the negative electrode composition.

12. a negative electrode current collector layer; and a negative electrode active material layer provided on one or both sides of the negative electrode current collector layer, The negative electrode active material layer comprises the negative electrode composition according to claim 9 or a cured product thereof.

13. The thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, 13. The negative electrode for a lithium secondary battery according to claim 12, wherein the negative electrode active material layer has a thickness of 5 μm or more and 500 μm or less.

14. positive electrode, A negative electrode for a lithium secondary battery according to claim 12 . A separator provided between the positive electrode and the negative electrode; and electrolyte, A lithium secondary battery comprising:

Citation Information

Patent Citations

  • Lithium secondary cell and fabrication method thereof

    JP2008034352A

  • Method for producing negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode material for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2012009421A

  • All-solid lithium ion secondary battery

    JP2019016517A

  • Silicon particles with specific chlorine content as active anode material for lithium-ion batteries

    JP2022504094A

  • Lithium secondary battery and method for manufacturing same

    WO2012132958A1